The house of make-believe : children's play and the developing imagination - Singer, Dorothy G. (Harvard University Press, 1990)
An attempt to cover all aspects of children's make-believe. The authors examine how imaginative play begins and develops and provide examples and evidence on the young child's invocation of imaginary friends, the adolescent's daring games and the adult's private imagery and inner thought.